Wind Power Integration on Interconnected or Isolated Upstream Facilities - Barbero, Santiago (2015)
In this paper electric studies considering an oil upstream facility with wind power and conventional generators are presented. Static power flows are performed. The voltage variations and reactive power requirements are analyzed. Also dynamic fault simulations, with and without the island formation are performed. The objective is to assess the impact of wind power generation to be included in a typical facility, in order to achieve a satisfactory performance. This work simulates a typical upstream facility, conformed by a 10.1 kV oil network a conventional motogenerator and different types of wind power plants. Wind turbine models and controls for electromechanical transients are used.